Perlindungan terhadap Hutan dalam Pelaksanaan Otonomi Daerah - Mujibussalim Mujibussalim (Kanun Jurnal Ilmu Hukum, 2010)
ABSTRACT: This research aims to find justified theories with regard to the governance regulation in the field of forestry based on local autonomy as regulated in the Constitution 1945, find out law protection towards the usage of forest resources in the context of the autonomy and to  obtain the concept of law regarding the protection of forest resources in the regulation of local autonomy. This is normative law research by applying historic and comparative legal research pointing at secondary data obtained from library research supported by primary data gathered from field research. This research is categorized as descriptive analysis research. The oblained data are analysed as juridical qualitative. The findings show that the regulation of forest resources has included te principles in accordance with sustainable development concept but it does not mean that the function of law as an engineering tool has been compatible with the purpose of the forestry management due to many evidences of deforestation. Practically, there is a conflict between central government and local government in therm of the authority of forest management, a lot deforestation causes forest amage in Indonesia, those facts show that the regulation regarding the authority of forest management ini the context of local autonomy implementation has not been able to protect the natural resources yet. The constraints faced are the law violations, lock of society participation in mking decision, collusion or conspiracy between businessman and bureacrats and security and lack of law enforcement. Forest Protection in the Local Autonomy Implementation